220k views
3 votes
Solve by completing the square. x2+6x−6=0

User Anti
by
5.3k points

2 Answers

2 votes

Answer:


x=-3\±√(15)

Explanation:

We have the following equation


x^2+6x-6=0

To use the method of completing squares you must take the coefficient of x and divide it by 2 and square the result.


((6)/(2))^2=9

Now add 9 on both sides of equality


(x^2+6x+ 9)-6=9

Factor the term in parentheses


(x+3)^2-6=9

Add 6 on both sides of the equation


(x+3)^2-6+6=9+6


(x+3)^2=15

Take square root on both sides of the equation


√((x+3)^2)=\±√(15)


x+3=\±√(15)

Subtract 3 from both sides of the equation.


x+3-3=-3\±√(15)


x=-3\±√(15)

User Lei Mou
by
5.4k points
3 votes

For this case we must solve the following equation by completing squares:


x ^ 2 + 6x-6 = 0

We add 6 to both sides of the equation:


x ^ 2 + 6x = 6

We divide the middle term by 2, and square it:


(\frac {6} {2}) ^ 2

And we add it to both sides of the equation:


x ^ 2 + 6x + (\frac {6} {2}) ^ 2 = 6 + (\frac {6} {2}) ^ 2\\x ^ 2 + 6x + (3) ^ 2 = 6 + 9

We rewrite the left part of the equation:


(x + 3) ^ 2 = 15

We apply root to both sides:


x + 3 = \pm \sqrt {15}

We have two solutions:


x_ {1} = \sqrt {15} -3\\x_ {2} = - \sqrt {15} -3

Answer:


x_ {1} = \sqrt {15} -3\\x_ {2} = - \sqrt {15} -3

User Ben Sharpe
by
4.9k points